The Effect of Project Based Learning (PJBL) Model on Elementary School Students' Computational Thinking Skills - Nabihah, Firyal Khoiroh; Andini, Wulan; Arifuddin, Ahmad (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
The low level of computational thinking skills among elementary school students in Indonesia poses a major challenge in 21st-century education. This study aims to analyze the effect of the Project Based Learning (PjBL) model on students' computational thinking skills. The research method used was a quantitative experiment with a pretest-posttest control group design. The research subjects consisted of two classes: an experimental class using the PjBL model and a control class using conventional methods. Data collection techniques included tests and observation. The t-test results showed a significant difference with a significance value of 0.000 < 0.05. The average post-test score of the experimental class was 82.13, while the control class was 68.75. Thus, the PjBL model is proven to be effective in improving elementary school students' computational thinking skills.